PATIENT’S SAFETY CULTURE: PRINCIPLES AND APPLICATIONS: REVIEW ARTICLE - Al Doweri, Haetham F; Al Raoush, Atef T; Alkhatib, Ahed J; Batiha, Mustafa Abdelrhman (European Scientific Journal, ESJ, 2015)
This study was conducted to review the literature towards patient’s safety culture in terms and applications. Patient’s safety is an essential component of healthcare quality. Even with continuous alertness, health care providers face many challenges in today’s health care environment in trying to keep patients safe. Patient’s safety is now a required subject that can provide feedback to the healthcare systems with the possibility of implementing improvement measures based on the identification of specific problems. The culture of patient’s safety can be analyzed at different levels of the healthcare system, through identifying strengths and weaknesses that configure the way that healthcare professionals think, behave and approach their work. Continuous evolutions in healthcare increase the importance of establishing and maintaining a culture of patient’s safety. Therefore research on safety culture is needed to raise awareness about the role of culture in promoting a safer environment. Patient’s safety culture examines how the perceptions, behaviors, and competencies of individuals and groups determine an organization’s commitment, style, and proficiency in health and safety management and it is used by organizations to determine targets for interventions to improve patient’s safety, evaluate the success of patient’s safety interventions, fulfill regulatory requirements, and conduct benchmarking. Patient’s safety culture is approached from different perspectives or dimensions such as reporting the frequency and severity of incidents, which so far are not taken into account by hospital staff. In this sense, an ongoing commitment must exist by management to promote and facilitate the culture of patient’s safety by providing the necessary tools to identify the most prevalent cultural patterns